Mobilizing against nuclear energy : a comparison of Germany and the United States - Joppke, Christian (Berkeley : University of California Press, 1993)
In the past two decades young people, environmentalists, church activists, leftists, and others have mobilized against nuclear energy. Anti-nuclear protest has been especially widespread and vocal in Western Europe and the United States. In this lucid, richly documented book, Christian Joppke compares the rise and fall of these protest movements in Germany and the United States, illuminating the relationship between national political structures and collective action. He analyzes existing approaches to the study of social movements and suggests an insightful new paradigm for research in this area. Joppke proposes a political process perspective that focuses on the interrelationship between the state and social movements, a model that takes into account a variety of forces, including differential state structures, political cultures, movement organizations, and temporal and contextual factors. This is an invaluable work for anyone studying the dynamics of social movements around the world.
Frontmatter -- Contents -- List of Figures and Tables -- Acknowledgments -- Abbreviations -- CHAPTER ONE. Introduction: Political Process and Social Movements -- CHAPTER TWO. Expert Dissent and Legal Intervention in the United States -- CHAPTER THREE. Elite Consensus and Citizen Initiatives in West Germany -- CHAPTER FOUR. Public-Interest Advocacy and Direct Action in the United States -- CHAPTER FIVE. Challenging the State in West Germany -- CHAPTER SIX. Three Mile Island and the Decline of Nuclear Power in the United States -- CHAPTER SEVEN. Institutionalization and New Militancy in West Germany -- CHAPTER EIGHT. Conclusion: Rethinking the Political Process Perspective -- APPENDIX A. Methodology -- APPENDIX B. Tables -- APPENDIX C. Informants and Primary Sources -- Notes -- Bibliography -- Index
Revision of author's theses (Ph. D.)--University of California at Berkeley, 1989.
Includes bibliographical references (pages 257-295) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Antinuclear movement -- United States; Antinuclear movement -- Germany; Social movements -- Political aspects; Mouvement antinucléaire -- États-Unis.; Mouvement antinucléaire -- Allemagne; Mouvements sociaux -- Aspect politique; social movements; TECHNOLOGY & ENGINEERING -- Power Resources -- Nuclear; HISTORY / United States / General; Antinuclear movement; Social movements -- Political aspects; Germany; United States; Business & Economics; Industries